Motivasi Berprestasi dengan Stres Kerja Pada Guru Taman Kanak-Kanak - Nafiah, Maulinda Nur; Laksmiwati, Hermien (Jurnal Psikologi Teori dan Terapan, 2016)
The purpose of this study was to determine the correlation between achievement motivation and working stress on kindergarten teachers in Sooko Subdistrict, Mojokerto Regency, East Java. The subjects were 53 kindergarten teachers who are theÂ  members of Ikatan Guru Taman Kanak-kanak Indonesia (IGTKI). Data collected using achievement motivation and working stress scales and analyzed using product moment correlation. The result shows that the coefficient correlation isÂ  -0,672 in the level of significant of 0,000 (pâ¤0,05). It means that there is significant negative correlation between achievement motivation and working stress. The result indicates that the higher achievement motivation correlates withÂ  the lower working stress. The achievement motivation gives 67,2% contribution in affecting working stress, while the rest 32,8% were contributed by other factors.Â Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara motivasi berprestasi dengan stres kerja pada guru Taman Kanak-Kanak di Kecamatan Sooko. Subjek penelitian ini adalah 53 guru Taman Kanak-Kanak anggota Ikatan Guru Taman Kanak-kanak Indonesia (IGTKI). Penelitian ini menggunakan instrumen skala motivasi berprestasi dan skala stres kerja yang dianalisis menggunakan korelasi product moment. Hasil analisis menunjukkan koefisien korelasi sebesar -0,672 pada level signifikansi 0,000 (pâ¤0,05). Hasil ini menunjukkan adanya korelasi negatif yang signifikan antara motivasi berprestasi dan stres kerja. Semakin tinggi motivasi berprestasi, maka akan semakin rendah stres kerja. Motivasi berprestasi memberikan kontribusi sebesar 67,2% pada stres kerja, dimana 32,8% dikontribusikan oleh variabel lain yang tidak diteliti dalam penelitian ini.